Genome-wide mapping of human loci for essential hypertension. - Caulfield, M; Munroe, P; Pembroke, J; Samani, N; Dominiczak, A; Brown, M; Benjamin, N; Webster, J; Ratcliffe, P; O'Shea, S; Papp, J; Taylor, E; et al. (2003)
BACKGROUND: Blood pressure may contribute to 50% of the global cardiovascular disease epidemic. By understanding the genes predisposing to common disorders such as human essential hypertension we may gain insights into novel pathophysiological mechanisms and potential therapeutic targets. In the Medical Research Council BRItish Genetics of HyperTension (BRIGHT) study, we aim to identify these genetic factors by scanning the human genome for susceptibility genes for essential hypertension. We describe the results of a genome scan for hypertension in a large white European population. METHODS: We phenotyped 2010 affected sibling pairs drawn from 1599 severely hypertensive families, and completed a 10 centimorgan genome-wide scan. After rigorous quality control, we analysed the genotypic data by non-parametric linkage, which tests whether genes are shared in excess among the affected sibling pairs. Lod scores, calculated at regular points along each chromosome, were used to assess the support for linkage. FINDINGS: Linkage analysis identified a principle locus on chromosome 6q, with a lod score of 3.21 that attained genome-wide significance (p=0.042). The inclusion of three further loci with lod scores higher than 1.57 (2q, 5q, and 9q) also show genome-wide significance (p=0.017) when assessed under a locus-counting analysis. INTERPRETATION: These findings imply that human essential hypertension has an oligogenic element (a few genes may be involved in determination of the trait) possibly superimposed on more minor genetic effects, and that several genes may be tractable to a positional cloning strategy.